Evolusi dan Arah Masa Depan Penelitian Model SCOR: Analisis Bibliometric pada Bidang Manajemen Rantai Pasok - Maya Permata Sari; Afifah, Afifah; Mega Dwi Septivani; Willson Gustiawan (MAMEN: Jurnal Manajemen, 2025)
This research aims to find out current and future research trends regarding supply chain performance measurement methods. Supply chain management is a vital component in the modern retail industry. In the face of fierce competition, retail companies are required to manage their supply chains efficiently in order to meet consumer demand quickly, maintain stock balance, and optimize distribution costs. SCOR is one of the methods commonly used to measure and evaluate supply chain performance. Bibliometric is an analytical approach that uses bibliographic data as an indicator to measure productivity, impact, and relationships between research entities. The two approaches used in this study are Bibliographic coupling and Co-Word Analysis. During June 2025, a search was carried out on the Scopus database and 202 documents were found according to predetermined criteria. Document processing uses the Vosviewer application which shows the visualization of a mesh diagram dividing the document into 4 clusters (red, yellow, green and blue) for analysis with the Bibliographic Coupling method which shows that the research trend on SCOR in the last two decades has focused on the use of SCOR for performance measurement and evaluation, integration of SCOR with other methods for strategy determination.  As for the Co-Word Analysis method, VosViewer groups documents into 3 clusters (red, green, blue) which shows the results that in the future SCOR research can be combined with technology and digitalization to map supply chain processes in order to achieve sustainability goals.